Effects of Abaloparatide‐SC on Fractures and Bone Mineral Density in Subgroups of Postmenopausal Women With Osteoporosis and Varying Baseline Risk Factors. (28th September 2016) - Cosman, Felicia; Hattersley, Gary; Hu, Ming‐yi; Williams, Gregory C; Fitzpatrick, Lorraine A; Black, Dennis M
ABSTRACT: Abaloparatide‐SC is a novel 34–amino acid peptide created to be a potent and selective activator of the parathyroid hormone receptor type 1 (PTHR1) signaling pathway. In the Abaloparatide Comparator Trial in Vertebral Endpoints (ACTIVE) Phase 3 trial (NCT01343004), abaloparatide reduced new morphometric vertebral fractures by 86% compared with placebo ( p  < 0.001) and nonvertebral fractures by 43% ( p  = 0.049) in postmenopausal women with osteoporosis. Abaloparatide‐SC increased bone mineral density (BMD) 3.4% at the total hip, 2.9% at the femoral neck, and 9.2% at the lumbar spine at 18 months (all p  < 0.001 versus placebo). The analysis reported here was designed to evaluate whether fracture risk reductions and BMD accrual were consistent across different levels of baseline risk. Risk factor subgroups were predefined categorically for BMD T ‐score of the lumbar spine, total hip, and femoral neck (≤–2.5 versus >–2.5 and ≤–3.0 versus >–3.0), history of nonvertebral fracture (yes versus no), prevalent vertebral fracture (yes versus no), and age (<65 versus 65 to <75 versus ≥75 years) at baseline. Forest plots show that there were no clinically meaningful interactions between any of the baseline risk factors and the treatment effect of abaloparatide‐SC on new morphometric vertebral fractures, nonvertebral fractures, or BMD increases. Abaloparatide provides protection against fractures consistently across a wide variety of ages and baseline risks, including those with and without prior fractures, and it has potential utility for a broad group of postmenopausal women with osteoporosis. © 2016 American Society for Bone and Mineral Research.